The Black Diamond - Young, Francis Brett, 1884-1954 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Black Diamond" by Francis Brett Young is a novel written in the early 20th century. It presents the life of Abner Fellows, a young boy growing up in a mining community, focusing on his complex relationship with his father and the various influences that shape his adolescence, including family dynamics and the allure of football. The narrative hints at societal themes, the struggles of working-class life, and the emergence of personal identity within the fabric of community life. The opening of the book introduces us to Abner's childhood in Halesby, where he lives with his father, John Fellows, a miner. It captures moments of Abner$1 (Bs innocent joy, such as attending football matches with his father and engaging in playful mischief with peers. The vivid imagery describes their environment, steeped in the realities of a coal mining town, and sets the stage for Abner's growth amid both playful moments and underlying tensions. His father, while proud and rough, is portrayed as a complex character whose relationship with Abner will become fraught as the narrative progresses. As Abner begins to navigate adolescence, alongside the domineering presence of his stepmother, Alice, and the influence of his friends, the groundwork is laid for the conflicts and developments that will follow in his journey toward manhood. (This is an automatically generated summary.)s
Release date is 2015-04-27
This ebook was transcribed by Les Bowler
Keywords: England -- Fiction; Coal miners -- Fiction; Man-woman relationships -- Fiction